Kajian Teknis Produktivitas Alat Gali-Muat dan Alat Angkut terhadap Pencapaian Target Produksi 33.792 LCM per Bulan pada Kegiatan Penambangan Andesit di PT XYZ Kecamatan Bojonegara, Kabupaten Serang, Provinsi Banten - Indra Anugrah Sidki (UNISBA Press, 2021)
Abstract. PT XYZ is a manufacturing industry company that has a mine located in the bojonegara sub-district, Serang district, which has a production operation IUP covering an area of 30 ha. The activity is carried out using the open pit mining method (quarry) with a production target of 33,792 LCM/month or 1,251.56 LCM/day by operating 2 excavators Komatsu PC-200 with a capacity of 0.9 LCM and 9 Hino Ranger FG 235 conveyances. JJ capacity 16 LCM. Several technical factors that can affect the achievement of production targets include work efficiency, circulation time and filling factor. So it is necessary to conduct a technical study to achieve the production target. Based on the results of the study, the productivity of 2 theoretical digging and loading equipment was 28,481.85 LCM/month, while the productivity of the conveyance in the condition of shedding material at Hopper was 7,973.50 LCM/month and the productivity of the conveyance in shedding conditions in Stock Raw was 20,398.68 LCM/month, then the total production of transportation equipment is 28,372.18 LCM/month. To achieve productivity, a technical study of improvements to the haul road geometry is carried out to estimate the reduction in cycle time. Where the circulation time of the conveyance is the shedding condition at Hopper from 41.97 minutes to 28.48 minutes and the shedding condition in Stock Raw from 37.86 minutes to 24.18 minutes. Then the productivity of the theoretical conveyance for shedding conditions at Hopper is 11,695.33 LCM/month and for shedding conditions in Stock Raw is 31,914.69 LCM/month, so the total is 43,610.02 LCM/month, so that the company's target can be achieved. Abstrak. PT XYZ adalah perusahaan industri manufaktur yang memiliki tambang berlokasi di kecamatan bojonegara, kabupaten Serang memiliki IUP opersi produksi seluas 30 Ha. Kegiatan dilakukan dengan menggunakan metode tambang terbuka (quarry) dengan target produksi sebesar 33.792 LCM/bulan atau 1.251,56 LCM/hari dengan mengoperasikan 2 alat gali-muat Excavator Komatsu PC-200 kapasitas 0,9 LCM dan 9 alat angkut Hino Ranger FG 235 JJ kapasitas 16 LCM. Beberapa faktor teknis yang dapat mempengaruhi tercapainya target produksi diantaranya efisiensi kerja, waktu edar dan faktor pengisian. Maka perlu dilakukan kajian teknis untuk mencapai target produksi. Berdasarkan hasil penelitian didapatkan produktivitas dari 2 alat gali-muat teoritis sebesar 28.481,85 LCM/bulan, sedangkan produktivitas alat angkut kondisi penumpahan material di Hopper sebesar 7.973,50 LCM/bulan dan produktivitas alat angkut kondisi penumpahan di Stock Raw 20,398.68 LCM/ bulan, maka total produksi alat angkut sebesar 28.372,18 LCM/bulan. Untuk mencapai produktivitas, maka dilakukan kajian teknis perbaikan terhadap geometri jalan angkut untuk mengestimasikan pengurangan waktu edar. Dimana waktu edar alat angkut kondisi penumpahan di Hopper dari 41,97 menit menjadi 28,48 menit dan kondisi penumpahan di Stock Raw dari 37,86 menit menjadi 24,18 menit. Maka didapatkan produktivitas alat angkut teoritis untuk kondisi penumpahan di Hopper sebesar 11.695,33 LCM/bulan dan kondisi penumpahan di Stock Raw sebesar 31.914,69 LCM/bulan, maka total sebesar 43.610,02 LCM/bulan, sehingga target perusahaan dapat tercapai.